Naming the “Brown Thing”: racial consciousness in the Ivory Tower - Mapaling, Curwyn; Shabalala, Nokulunga (Frontiers in Education, 2025)
IntroductionThis paper explores the ethical and emotional dimensions of engaging critical racial consciousness in South African higher education. Racialised educators, particularly Black academics, continue to navigate pedagogical spaces shaped by institutional Whiteness, subtle yet persistent norms that privilege Eurocentric standards and misrecognize non-White authority and experience.MethodsUsing collaborative autoethnography and critical incident analysis, two Black academics engaged in a series of recorded reflective conversations. These dialogues served as both data and analytic spaces. Through retrospective discussion, ethically charged incidents from teaching and supervision were identified, revisited and interpreted.ResultsThe narratives reveal how misrecognition and racialised silencing surface in everyday academic encounters, through both overt critique and quiet erasure. These moments disrupt normative routines and compel educators to examine their complicity, positionality and pedagogical stance. Key themes include the emotional labor of teaching, the tension between care and compliance, and the institutional conditions that render Black authority negotiable.DiscussionRather than seeking closure, the paper argues for staying with the discomfort of ethical ruptures as a pedagogical and political strategy. It positions critical reflection and vulnerability as necessary for decolonial praxis. We propose that humanizing education begins by naming the “Brown Thing”: the embodied, affective, and often unspoken realities of race in the Ivory Tower.